Efectos de la intervención del programa de emprendimientos rurales inclusivos del FONCODES en el desarrollo social de Manacamiri 2023 - García Pinchi, Segundo Alejandro (2025)
The main purpose of this research was to determine the effects of the FONCODES inclusive rural entrepreneurship program intervention on the social development of Manacamiri 2023. An applied research approach and a non-experimental study design were chosen. The study group included 140 individuals who completed a questionnaire as an instrument to measure the different variables. The results show that the effects of the intervention of the inclusive rural entrepreneurship program implemented by FONCODES is regular at 26%. For its part, the level of social development is regular, rated as (26%). Finally, it is concluded that there is a positive impact between the variables, this program predicts the behavior of social development by 79.8%; Likewise, the technical training service dimension has a predictive power of 64.6% on social development, contributing positively to SD; For its part, service for the development of productive capacities with an explanatory capacity of 68.1%, strengthening the D.S; Also, the service for the development of rural enterprises is estimated to predict the behavior of social development by 48.6%; Finally, the impact generated on social development implies the participation of 59.2% of the asset endowment, suggesting that this process can significantly influence the social development of the community.